Short communication. Use of 4-(5-Br-2 pyridylazo) -1,3-diaminobenzene (5-Br-PADAB) for the spectrometric determination of cobalt in wine - Baudino, O.M.=700 1 De Pedernera, M.M.; Guardia Calderon, C.E.; Suero, E.A.
Es, En)
Ilus., 13 ref.
Keywords: TECNICAS ANALITICAS; BEBIDAS ALCOHOLICAS; VINOS; METALES PESADOS; ESPAÑA; ABSORCIOMETRIA